Hydroclimatic extremes and food security hotspots in West Africa: evidence from rainfall–yield interactions - Obahoundje, Salomon; Tilahun, Seifu A.; Schmitter, Petra (Frontiers Media, 2025)
Introduction: Rainfall regimes across West Africa have undergone substantial transformations over the past four decades, with profound implications for rainfed agriculture and food security. However, limited understanding persists on how rainfall extremes translate into spatially differentiated crop yield responses across agroclimatic zones.